2022
DOI: 10.1007/s11356-022-18846-3
|View full text |Cite
|
Sign up to set email alerts
|

Wetting mechanism and morphological adaptation; leaf rolling enhancing atmospheric water acquisition in wheat crop—a review

Abstract: Several plant species such as grasses are dominant in many habitats including arid and semi-arid areas. These species survive in these regions by developing exclusive structures, which helps in the collection of atmospheric water. Before the collected water evaporates, these structures have unique canopy structure for water transportation that plays an equivalent share in the fog-harvesting mechanism. In this review, the atmospheric gaseous water harvesting mechanisms and their affinity of measurements were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 167 publications
(193 reference statements)
0
19
0
Order By: Relevance
“…[ 63 ] had reported that wheat leaf rolling and its association with leaf surface wetness helps the plant in water retention. In wheat, leaf rolling facilitates efficient photosynthetic activities and enhances accumulation of dry matter [ 64 , 65 ], lowers leaf surface temperature and reduces water loss by slowing down transpiration [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 63 ] had reported that wheat leaf rolling and its association with leaf surface wetness helps the plant in water retention. In wheat, leaf rolling facilitates efficient photosynthetic activities and enhances accumulation of dry matter [ 64 , 65 ], lowers leaf surface temperature and reduces water loss by slowing down transpiration [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leaf wetting has both positive and negative effects on plant growth and development. Wettability of the leaf surfaces can have a positive effect by supplying water through water absorption or transpiration suppression and improve plant water status (Eller et al 2013 ; Goldsmith et al 2013 ; Gotsch et al 2014 ; Ali et al 2022 ). Alternatively, negative effects inhibit leaf gas exchange, nutrients leaches, and promote pathogen growth on the leaf surfaces (Bradley et al 2003 ; Sase et al 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Song et al [42] also found that drought stress at different critical growth stages caused severe losses to the plant growth and yield and its severity depended on the stage of growth at which it occurred. There are other previous studies on wheat crops related to soil, which showed a positive impact under drought and other climatic conditions [43][44][45][46][47]. There are numerous other studies under the same climatic conditions showing the confirmation that soil conditioning materials including biochar and soil conditioner improve the soil properties and are helpful for nitrogen uptake and water-related soil properties in different crops [48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 89%